Case report: Suspected organizing pneumonia secondary to severe respiratory syncytial virus pneumonia in an elderly patient - Feng, Min; Zhang, Jie; Li, Xiangrui; Wang, Shuai; Li, Yanxia; Dong, Chang (Frontiers in Medicine, 2024)
In recent years, it has gradually become an important pathogen of lower respiratory tract infection in elderly people with an underlying disease. However, at present, the treatment of severe RSV pneumonia in adults is unclear, and organizing pneumonia (OP) after severe RSV infection has rarely been reported. We reported a 76-year-old man with multiple chronic heart and lung diseases who presented with fever, cough and progressive dyspnea. Finally, severe RSV pneumonia was diagnosed after his nasopharyngeal swabs and bronchoalveolar lavage metagenomic next-generation sequencing tests were positive for RSV. After combined treatment with oral ribavirin, intravenous immunoglobulin and corticosteroids, the patient's condition largely resolved, and he was discharged. However, when the corticosteroids were gradually tapered, the disease relapsed twice, and the patient experienced fever and aggravated dyspnea. Despite the lack of pathological evidence, we highly suspected organizing pneumonia secondary to severe RSV pneumonia based on the typical imaging manifestations and the clinical characteristics of a good response to corticosteroids. Finally, this patient was successfully treated with a course of corticosteroids and followed up for 14 months in total.